Sociocultural Appearance Standards and Risk Factors for Eating Disorders in Adolescents and Women of Various Ages - Izydorczyk, Bernadetta; Sitnik-Warchulska, Katarzyna (Frontiers in Psychology, 2018)
The main aim of the present study was to verify the level of impact socio-cultural appearance standards (passive awareness and active internalization) have on body dissatisfaction, the desire to engage in a relentless pursuit of thinness, the adoption of a perfectionistic attitude towards the body, and the development of a tendency to engage in bulimic eating behavior, which can develop in adolescent girls and women of varying ages. The study group comprised 234 individuals: 95 secondary school girls, 33 high school girls, 56 female students, and 50 employed women, all of whom were living in southern Poland. Participants were not diagnosed with any psychiatric disorders (including eating disorders). The variables were measured using the Polish version of Garner’s Eating Disorder Inventory and the Polish Sociocultural Attitudes Towards Physical Appearance and Body Image Inventory (based on the SATAQ-3). The findings revealed that the youngest Polish girls (aged 12-15) reported the highest level of risk factors for eating disorders. Among the entire study group, the internalization of appearance standards and the pressure associated with various media messages were determined to be predictors of the pursuit of thinness, regardless of age and BMI values. The second most significant variable explained by the internalization of socio-cultural standards was body dissatisfaction. The internalization of socio-cultural norms provided a significant explanation of bulimic tendencies only in the youngest girls. Perfectionism proved not to be affected by the socio-cultural impact of mass media. The adult women had the lowest average scores over the entire study population regarding exposure frequency to body images in mass media and regarding the experience of pressure exerted by socio-cultural norms. The high level of internalization of socio-cultural appearance standards seems to be significantly linked to body satisfaction in women aged 30 and older. Young adolescent girls constitute a high-risk group for a specific psychological proneness to developing eating disorders as a result of the socio-cultural influence exerted by mass media. The obtained study results can prove helpful in creating education programmes in preventive healthcare aimed particularly at the youngest adolescents.